Self-Employment and Geographical Mobility in Germany - Darja Reuschke (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Little is known about the individual location behaviour of self-employed entrepreneurs. This paper investigates the geographical mobility behaviour of self-employed entrepreneurs, as compared to employees, thereby shedding new light onto the place embeddedness of self-employment. It examines whether self-employed entrepreneurs are "rooted" in place and also whether those who are more rooted in place are more likely to enter self-employment. The paper draws on large-scale panel data covering the years 1996-2009 from the German Socio-Economic Panel Study (SOEP). It shows that self-employed entrepreneurs as compared to employeesare not more "rooted" in their place of residence and that those who are more rooted in their place of residence are not more likely to become self-employed. However, in contrast to expectations drawn from previous literature, flows into self-employment are positively associated with inter-regional moves. It concludes that a longitudinal perspective on individual employment careers provides an important methodological advance. In addition, it emphasises the importance of mobility and immobility and individual and household constraints and preferences for understanding who becomes self-employed.
Keywords: C23; J21; J61; J62; R23; 330; Self-employment; migration; moves; panel data; SOEP; Germany; Selbstständige; Unternehmer; Binnenwanderung; Vergleich; Arbeitsmobilität; Deutschland